Cadmium chloride down-regulates the expression of Rad51 in HC11 cells and reduces knock-in efficiency - Ga-Yeon Kim; Man-Jong Kang (The Korean Society of Animal Reproduction and Biotechnology, 2023)
Background: Efficient gene editing technology is needed for successful knock-in. Homologous recombination (HR) is a major double-strand break repair pathway that can be utilized for accurately inserting foreign genes into the genome. HR occurs during the S/G2 phase, and the DNA mismatch repair (MMR) pathway is inextricably linked to HR to maintain HR fidelity. This study was conducted to investigate the effect of inhibiting MMR-related genes using CdCl2, an MMR-related gene inhibitor, on HR efficiency in HC11 cells. Methods: The mRNA and protein expression levels of MMR-related genes (Msh2, Msh3, Msh6, Mlh1, Pms2), the HR-related gene Rad51, and the NHEJ-related gene DNA Ligase IV were assessed in HC11 cells treated with 10 μM of CdCl2 for 48 hours. In addition, HC11 cells were transfected with a CRISPR/sgRNA expression vector and a knock-in vector targeting Exon3 of the mouse-beta casein locus, and treated with 10 μM cadmium for 48 hours. The knock-in efficiency was monitored through PCR. Results: The treatment of HC11 cells with a high-dose of CdCl2 decreased the mRNA expression of the HR-related gene Rad51 in HC11 cells. In addition, the inhibition of MMR-related genes through CdCl2 treatment did not lead to an increase in knock-in efficiency. Conclusions: The inhibition of MMR-related gene expression through high-dose CdCl2 treatment reduces the expression of the HR-related gene Rad51, which is active during recombination. Therefore, it was determined that CdCl2 is an inappropriate compound for improving HR efficiency.